Solitary unbroken by four decades in solitary confinement : my story of transformation and hope - Woodfox, Albert 1947-2022; George, Leslie (Grove Press, 2019)
Nearly forty years in solitary confinement in a 6-foot by 9-foot cell for 23 hours a day for a crime he did not commit, Albert Woodfox survived and emerged with his humanity and sense of hope for the future intact